Analisis Perilaku Memilih Pada Pemilih Pemula Menjelang Pemilu 2024 Melalui Penerapan Konsep Voting Advice Application - Malau, Meyta Elisabeth; Rikin, M. Rafli; Kartika, Hansen Sukma; Ardiansa, Dirga (Talenta Publisher, 2024)
The 2024 election moment is an opportunity for voting advice applications (VAA) to help them making wise political choices since it will be filled with many first-time voters. However, the development of VAA in Indonesia requires an understanding of voting behavior in order to be able to provide appropriate advice to users. For this reason, this research aims to determine the voting behavior of first-time voters so that VAA developers will gain a good understanding of the needs of first-time voters in making political choices byÂ distributing national survey and focus group discussion to first-time voters. This research finds that VAA succeeds in presenting willingness to vote, discuss, and act on their first-time voter users, who also have more dominant rational voting behavior despite their low level of knowledge, liking, and urge to vote towards political parties. Corruption eradication, gender,and education issues are the main concerns of first-time voters. Hopefully, the more appropriate VAA works to the issue preferences of first-time voters, the more it will encourage the creation of well-informed choice voters in Indonesia.